(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This thesis analyzes the constitutional and legal guarantees of the unity of the economic space, as well as the free movement of goods, services, labor resources, and financial funds throughout the territory of the country, as enshrined in the newly revised Constitution of the Republic of Uzbekistan. Within the scope of the research, the issues of eliminating artificial administrative barriers in the domestic market, restricting the improper interference of local government authorities in market mechanisms, and legally ensuring interregional economic integration are elucidated on the basis of the principle of moving from the general to the specific.